The Impact of Interactive Mobile Technology on Enhancing Self-Management and Autonomous Learning Abilities in Higher Education - Li, Jingyi; Liu, Huiyuan (International Journal of Interactive Mobile Technologies (iJIM), 2026)
In the digital transformation process of vocational education, interactive mobile technology has become a key support for enhancing the autonomous learning abilities of vocational college students. This study, based on situational intelligence theory, social constructivism, and metacognitive theory, constructs a three-dimensional ecological framework comprising situational awareness and adaptation, social regulatory networks, and dynamic metacognitive scaffolding. It systematically reveals the internal mechanisms through which mobile technology empowers self-management and autonomous learning in vocational students. Using a mixed-methods research approach, the study investigates the application effectiveness of a mobile learning system guided by this framework, with a sample of 286 students from three vocational colleges. The results show that the framework significantly improves students’ abilities in goal-setting, time management, strategy regulation, and reflective correction. Furthermore, the precise adaptation of situational awareness, the mutual support of social networks, and the personalized guidance of dynamic scaffolding have synergistic effects. The application of technology shows heterogeneity among different student groups based on professional types and learning foundations. The findings provide theoretical foundations and practical references for the development of mobile learning resources in vocational education, the design of intelligent learning platforms, and the innovation of autonomous learning cultivation models.